Formulasi sabun mandi cair berbahan alami menggunakan pendekatan liquid soap base: systematics literature review - Zamza, Nuri Indria Khofidatus (Maliki Interdisciplinary Journal, 2025)
This study systematically reviews the formulation of natural ingredient-based liquid bath soap using a liquid soap base approach through a Systematic Literature Review (SLR) method. The review examines scientific articles from the last five years related to liquid soap formulation with a particular focus on the use of natural active ingredients and their effectiveness. The findings reveal that the incorporation of natural materials such as plant extracts, vegetable oils, and other natural additives offers functional benefits, enhances product quality, and supports sustainability principles. The combination of natural ingredients with liquid soap base provides advantages in terms of gentleness, safety, and added benefits such as antibacterial and antioxidant properties. However, research gaps remain regarding formulation stability and long-term safety assessments, which have not been comprehensively explored.